Bachon ke liye qissas anbiya: hazrat nuh as - Safdar, Shaheen; Samra, Kamran Hina, Ghafor (Children Publication Karachi, 2006)
A children's book that narrates the stories of various Prophets in a simple and engaging manner Providing valuable lessons in faith, courage, and wisdom. The book is designed to inspire young minds by bringing the stories of these revered figures to life with easy-to-understand language and illustrations.